The complete chloroplast genome sequence of Habenaria ciliolaris (Orchidaceae) - Chen, Ming-Kun (Mitochondrial DNA B Resour, 2019)
Habenaria ciliolaris is a kind of orchid with ornamental value. In this study, we reported the complete chloroplast genome of H. ciliolaris. The complete chloroplast genome is 154,544 bp in length, consists of a pair of inverted repeat (IR, 25,455 bp) regions, a large single-copy region (LSC, 84,032 bp) and a small single-copy region (SSC, 19,602 bp). It contains 179 genes, including 133 protein-coding genes, 38 tRNAs, and 8 rRNAs. A maximum-likelihood phylogenetic analysis demonstrated a close relationship between H. ciliolaris and Habenaria radiata. This work will be valuable for genetic and phylogenetic studies on H. ciliolaris.